1876 Wyo. Comp. Laws 352, An Act to Prevent the Carrying of Fire Arms and Other Deadly Weapons, ch. 52, § 1-3. - (:unkn) unknown (My University, 1876)
That hereafter it shall be unlawful for any resident of any city, town or village, or for any one not a resident of any city, town or village, in said territory, but a sojourner therein, to bear upon his person, concealed or openly, any fire arm or other deadly weapon, within the limits of any city, town or village.
Keywords: CARRY